Temperature dependence of the first order Raman scattering in thin films of mc-Si:H - Cerqueira, M. F. (1999)
The temperature effect on microcrystalline silicon (mc-Si:H) films produced by R.F. magnetron sputtering has been studied by Raman spectroscopy. The thermal behaviour of mc-Si:H films and crystalline silicon is compared and interpreted on the basis of anharmonic effects. We have studied the first order Raman spectra of our films for several Ar+ laser powers. Our results show a blue shift and a broadening of the Raman spectra with increasing the laser power. This effect is not due to structural changes since it is reproducible. The sample temperature has been calculated according to the well known relation between Stokes and anti-Stokes components. Our results show that the temperature effect is stronger in mc-Si:H than in crystalline silicon. This difference can be attributed to the size of the microcrystals, which are imbedded in a amorphous matrix surrounded by a third phase called grain boundary.